2021
DOI: 10.1139/cjps-2019-0314
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and translocation of dicamba in dicamba-tolerant wild tomato

Abstract: Herbicide tolerance is commonly associated with reduced absorption and translocation of the herbicide; we hypothesized that the mechanism of dicamba tolerance in wild tomato (Solanum lycopersicum) accessions is due to these. The absorption and translocation of dicamba were investigated at a drift rate of 2.8 g ae ha-1, in three predetermined dicamba-tolerant wild accessions (TOM199, TOM198, and TOM300), and compared with two dicamba-susceptible (DS) commercial tomato cultivars [Money Maker (MM) and Better Boy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Similarly, in our previous study (Zangoueinejad et al 2020a), we indicated that TOM198, TOM199, and TOM300 absorbed a lower amount of dicamba than two commercial tomato cultivars (Better Boy and Money Maker) after herbicide application at the drift rate (2.8 g ae ha -1 ). However, no difference in the herbicide distribution pattern was observed between them.…”
Section: Absorption and Distributionsupporting
confidence: 83%
“…Similarly, in our previous study (Zangoueinejad et al 2020a), we indicated that TOM198, TOM199, and TOM300 absorbed a lower amount of dicamba than two commercial tomato cultivars (Better Boy and Money Maker) after herbicide application at the drift rate (2.8 g ae ha -1 ). However, no difference in the herbicide distribution pattern was observed between them.…”
Section: Absorption and Distributionsupporting
confidence: 83%
“…Sirons et al (1982) reported the persistence of dicamba residue on tomato plants exposed to five rates of dicamba ranging from 1.1 to 112 g ha −1 , but the studies were conducted in a growth chamber, and it is unclear whether the homogenized plant sample used for residue testing included tomato fruits. Zangoueinejad et al (2020) applied 2.8 g ha −1 dicamba to susceptible and resistant tomato lines in a greenhouse study and documented differences in herbicide uptake and partitioning within young plants at 1, 3, and 7 DAT, but did not report on dicamba residue partitioning in tomato fruits. Therefore, the objective of this study was to determine the persistence of dicamba and select metabolites from tomato shoot and fruit tissues following exposure to reduced rates of dicamba under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pronamide was extracted using a method similar to that of Zangoueinejad et al (2020). Foliage and root samples were cut into 5-mm segments with scissors and placed in 2-ml microcentrifuge tubes (Avantor, Radnor, PA) and were weighed to 0.10 g using an analytical scale (Mettler Toledo AE260, Marshall Scientific, Hampton, NH).…”
Section: Foliar-only Application Of Pronamidementioning
confidence: 99%